Creativity and gaze behaviour in football - Stephan Zahno (Current Issues in Sport Science, 2023)
Performing creative actions is considered a decisive element in football. Recent studies have suggested that football players’ creativity is underpinned by a specific visual search strategy (e.g., Roca et al., 2021). Specifically, studies showed that players who scored high in a football-specific creativity task used more fixations of shorter durations than players who scored low. In the creativity task, players were asked to name as many solution ideas as possible. From an applied perspective, the questions arise: is this gaze strategy generally beneficial to perform creative actions? Should this gaze pattern be trained to improve creativity?